ATP Modifies the Proteome of Extracellular Vesicles Released by Microglia and Influences Their Action on Astrocytes - Drago, Francesco; Lombardi, Marta; Prada, Ilaria; Gabrielli, Martina; Joshi, Pooja; Cojoc, Dan; Franck, Julien; Fournier, Isabelle; Vizioli, Jacopo; Verderio, Claudia (Frontiers in Pharmacology, 2017)
Extracellular ATP is among molecules promoting microglia activation and inducing the release of extracellular vesicles (EVs), which are potent mediators of intercellular communication between microglia and the microenvironment. We previously showed that EVs produced under ATP stimulation (ATP-EVs) propagate a robust inflammatory reaction among astrocytes and microglia in vitro and in mice with subclinical neuroinflammation (1). However, the proteome of EVs released upon ATP stimulation has not yet been elucidated. In this study we applied a label free proteomic approach to characterize the proteome of EVs released constitutively and during microglia activation with ATP. We show that ATP drives sorting in EVs of a set of proteins implicated in cell adhesion/extracellular matrix organization, autophagy-lysosomal pathway and cellular metabolism, that may influence the response of recipient astrocytes to EVs. These data provide new clues to molecular mechanisms involved in microglia response to ATP and in microglia signalling to the environment via EVs.